Compensation challenges in early childhood education: an analysis of Mississippi’s child care workforce - Katerina Sergi; John Stephen McCown; Mary Rebecca Read-Wahidi; Ismail H. Yigit; Callie Poole; Heather Hanna (International Journal of Child Care and Education Policy)
Abstract The early childhood workforce in the U.S. faces significant challenges, including low wages, high turnover, and inadequate support, affecting the quality of education and care for children. The existing research on early childhood education typically identifies low wages as an issue, but lacks advanced analysis of rural–urban pay disparities and how educational qualifications interact with location to affect compensation. This leaves a significant gap in understanding wage compression across the early childhood education (ECE) field. Utilizing the framework of wage compression, which posits that higher qualifications may not equate to higher pay, this study uses data from the 2023 Mississippi Wages Survey to analyze how job experience, educational attainment, and geographic location impact wages for early childhood educators. The results show that average hourly wages for teachers are approximately $10.93, significantly below national standards. Hourly compensation in large urban areas reaches $11.66, as compared to $11.02 and $9.95 per hour in rural and small urban areas respectively. Years of experience, educational attainment, and geography show the modest effects on wage differences. Higher education correlates with better pay; however, wage increases remain modest, indicating policies targeting only education may insufficiently address compensation issues. Geographic disparities exist, with urban areas generally offering higher wages than rural ones, but small urban areas report lower pay than expected. These findings underscore systemic undervaluation and necessitate policy interventions, such as wage increases and support for professional development, tailored to local contexts, to enhance workforce stability and childcare quality. Wage reforms and increased funding can contribute to elevating the profession. Future research should include longitudinal studies across multiple states for a comprehensive understanding of these issues.